The effect of branched-chain amino acid on muscle damage markers and performance following strenuous exercise: a systematic review and meta-analysis - Doma, K.; Singh, U.; Boullosa, D.; Connor, J. D. (Applied Physiology, Nutrition, and Metabolism, 2021)
This systematic review and meta-analysis determined whether the ergogenic effects of branched-chain amino acids (BCAA) ameliorated markers of muscle damage and performance following strenuous exercise. In total, 25 studies were included, consisting of 479 participants (age 24.3 ± 8.3 years, height 1.73 ± 0.06 m, body mass 70.8 ± 9.5 kg, females 26.3%). These studies were rated as fair to excellent following the PEDro scale. The outcome measures were compared between the BCAA and placebo conditions at 24 and 48 hours following muscle-damaging exercises, using standardised mean differences and associated p-values via forest plots. Our meta-analysis demonstrated significantly lower levels of indirect muscle damage markers (creatine kinase, lactate dehydrogenase and myoglobin) at 48 hours post-exercise (standardised mean difference [SMD] = -0.41; p < 0.05) for the BCAA than placebo conditions, whilst muscle soreness was significant at 24 hours post-exercise (SMD = -0.28 = d = -0.61; p < 0.05) and 48 hours post-exercise (SMD = -0.41 = d= -0.92; p < 0.01). However, no significant differences were identified between the BCAA and placebo conditions for muscle performance at 24 or 48 hours post-exercise (SMD = 0.08 = d = 0.21; p > 0.05). Overall, BCAA reduced the level of muscle damage biomarkers and muscle soreness following muscle-damaging exercises. However, the potential benefits of BCAA for muscle performance recovery is questionable and warrants further investigation to determine the practicality of BCAA for ameliorating muscle damage symptoms in diverse populations. PROSPERO registration number: CRD42020191248. Novelty: • BCAA reduces the level of creatine kinase and muscle soreness following strenuous exercise with a dose-response relationship. • BCAA does not accelerate recovery for muscle performance.